Effects of Side Flushing and Multi-Aperture Inner Flushing on Characteristics of Electrical Discharge Machining Macro Deep Holes - Suppawat Chuvaree; Kannachai Kanlayasiri (Metals, 2021)
This research investigates the effect of machining parameters on material removal rate, electrode wear ratio, and gap clearance of macro deep holes with a depth-to-diameter ratio over four. The experiments were carried out using electrical discharge machining with side flushing and multi-aperture flushing to improve the machining performance and surface integrity. The machining parameters were pulse on-time, pulse off-time, current, and electrode rotation. Response surface methodology and the desirability function were used to optimize the electrical discharge machining parameters. The results showed that pulse on-time, current, and electrode rotation were positively correlated with the material removal rate. The electrode wear ratio was inversely correlated with pulse on-time and electrode rotation but positively correlated with current. Gap clearance was positively correlated with pulse on-time but inversely correlated with pulse off-time, current, and electrode rotation. The optimal machining condition of electrical discharge machining with side flushing was 100 µs pulse on-time, 20 µs pulse off-time, 15 A current, and 70 rpm electrode rotation; and that of electrical discharge machining with multi-aperture flushing was 130 µs, 2 µs, 15 A, and 70 rpm. The novelty of this research lies in the use of multi-aperture flushing to improve the machining performance, enable a more uniform GC profile, and minimize the incidence of recast layer.
Keywords: Advanced Machining and Optimization Techniques; Advanced machining processes and optimization; Advanced Surface Polishing Techniques